2006
DOI: 10.1088/0953-2048/19/2/011
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and analysis for a small-sized flywheel energy storage system with a high-temperature superconductor bearing

Abstract: This paper presents a small-sized flywheel energy storage system that uses a high-temperature superconductor (HTS) bearing characterized by a non-contacting bearing with no active control. The small-sized flywheel is made up several magnets for a motor/generator as well as an HTS bearing, and they are fitted into a 34 mm diameter, 3 mm thick aluminium disc. For simplicity and miniaturization of the whole system, the small-sized flywheel takes torque directly from a planar stator, which consists of an axial flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In our previous paper, we concentrated on a small-capacity energy storage system for micro-satellites and demonstrated that a small-sized flywheel levitates and rotates above the HTS [8][9][10]. In the first design of the flywheel, the motor and bearing magnets were located in the same plane.…”
Section: Previous Resultsmentioning
confidence: 99%
“…In our previous paper, we concentrated on a small-capacity energy storage system for micro-satellites and demonstrated that a small-sized flywheel levitates and rotates above the HTS [8][9][10]. In the first design of the flywheel, the motor and bearing magnets were located in the same plane.…”
Section: Previous Resultsmentioning
confidence: 99%